Mechanisms of manganese uptake and long-distance transport in the hyperaccumulator Celosia argentea Linn. - Wenxuan Jiang; Pingping Jiang; Shaohong You; Hui Qiu; Jie Liu; Xuehong Zhang; Mouyixing Chen (Ecotoxicology and Environmental Safety)
Celosia argentea Linn. is a hyperaccumulator for the remediation of manganese (Mn)-contaminated soil owing to its rapid growth, high decontamination capacity, and strong stress resistance. However, little is known about the processes involved in long-distance transport of Mn in hyperaccumulators. In this study, synchrotron-based micro X-ray fluorescence (μ-XRF) imaging showed that root tips and root hairs may be the focal sites for root uptake of Mn. Furthermore, the high Mn intensity in the vascular bundles (xylem and phloem) of stems and petioles indicates that the xylem and phloem play crucial roles in Mn transport from roots to leaves. High concentrations of Mn and three organic acids (oxalic, citric, and malic) were detected in the xylem sap under Mn treatment, and Mn may be chelated with them in the xylem for transport from the root to the shoot. Additionally, rooting and leaf-sourcing experiments confirmed that accumulated Mn in mature leaves could be re-transported via the phloem. However, the majority of Mn exported from mature leaves was translocated upward to the shoots (approximately 96 %), and only 4 % was translocated to the roots. These results provide new insights into the mechanisms of long-distance transport of Mn in plants.